Unusual Cause of Intestinal Obstruction: Left Paraduodenal Hernia - Sami Akbulut (Case Reports in Medicine)
Internal intestinal hernia has been defined as bulging of the intestines through a normal or an abnormal peritoneal or mesenteric opening. Paraduodenal hernias comprise 30%–53% of all internal intestinal herniations and account for 0.2%–0.9% of all bowel obstructions. In this paper, we aimed to present a male patient of 42 years of age who developed intestinal obstruction due to left paraduodenal hernias. Left paraduodenal hernia should be taken into consideration in the differential diagnosis in patients of relatively younger ages with no prior abdominal surgery who frequently have bowel obstruction episodes.